Perlindungan Hukum Anak Selaku Korban Perkosaan Sebagai Pelaku Aborsi - Yunika Rosa Rehan Ashari; Fuadi Isnawan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study discusses the form of responsibility and legal protection of children as perpetrators of criminal acts of abortion as well as the victim of rape. The author uses normative methods with legislation approach, case approach, and conceptual approach. The results of the study showed the form of criminal liability for child rape victims as perpetrators of abortion based on Muara Bulian District Court decision Number 5/Pid.Sus.Children/2018 / PN Mbn explained Article 77 a paragraph (1) Jo article 45A of Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 concerning the protection of children Jo. Article 55 paragraph (1) to-1 of the Criminal Code. Legal protection that can be provided for children include rehabilitation for psychological trauma victims and the release of victims from all criminal charges in the Jambi High Court decision with Case Number 6/Pid.Sus-Anak/2018 / PT JMB, listed in Article 59 Paragraphs (1) and (2), 59A and Article 64 letter G of Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning child protection. However, on this matter there is no legislation that definitively gives permission for children who are victims of rape or sexual violence to have abortions, because there are still children who must carry out accountability for actions outside of their will as victims.